Pemutusan Perjanjian Secara Sepihak dalam Hukum Perikatan Indonesia Ditinjau dari Akibat Hukum dan Perlindungan terhadap Pihak yang Dirugikan - Kayla Vania Gita Putri (Program Studi Ilmu Hukum, Universitas Kuningan, 2026)
Unilateral termination of an agreement is one of the issues frequently encountered in Indonesian civil law practice, as it may create legal uncertainty and cause losses to the parties bound by the agreement. Although the Indonesian Civil Code has regulated the mechanism for contract cancellation, differences in its application remain, particularly regarding the legal consequences and the forms of legal protection available to the aggrieved party. This study aims to analyze the legal consequences of unilateral termination of an agreement and the legal protection that may be afforded to the injured party under Indonesian contract law. This research employs a normative legal research method using statutory and conceptual approaches through library research on primary, secondary, and tertiary legal materials. The findings indicate that, in principle, unilateral termination of an agreement contravenes the principle of pacta sunt servanda as stipulated in Article 1338 of the Indonesian Civil Code. Furthermore, cancellation of an agreement due to breach of contract must generally be requested through the court pursuant to Article 1266 of the Indonesian Civil Code. Therefore, unilateral termination carried out without following the prescribed legal procedure may result in the agreement remaining legally binding, the obligation to pay damages, and even the possibility of being classified as a tort if conducted in bad faith. Legal protection for the aggrieved party may be pursued through claims for specific performance, cancellation of the unlawful termination, compensation for damages, and the application of the principles of good faith, fairness, and justice in dispute resolution.